Medicinal chemistry perspective of pyrido[2, 3-d]pyrimidines as anticancer agents. Issue 10 (28th February 2023) - Kumar, Adarsh; Bhagat, Kuber Kumar; Singh, Ankit Kumar; Singh, Harshwardhan; Angre, Tanuja; Verma, Amita; Khalilullah, Habibullah; Jaremko, Mariusz; Emwas, Abdul-Hamid; Kumar, Pradeep
Abstract : Pyrido[2, 3- d ]pyrimidines against various types of cancer. Abstract : Cancer is a major cause of deaths across the globe due to chemoresistance and lack of selective chemotherapy. Pyrido[2, 3- d ]pyrimidine is an emerging scaffold in medicinal chemistry having a broad spectrum of activities, including antitumor, antibacterial, CNS depressive, anticonvulsant, and antipyretic activities. In this study, we have covered different cancer targets, including tyrosine kinase, extracellular regulated protein kinases – ABL kinase, phosphatidylinositol-3 kinase, mammalian target of rapamycin, p38 mitogen-activated protein kinases, BCR-ABL, dihydrofolate reductase, cyclin-dependent kinase, phosphodiesterase, KRAS and fibroblast growth factor receptors, their signaling pathways, mechanism of action and structure–activity relationship of pyrido[2, 3- d ]pyrimidine derivatives as inhibitors of the above-mentioned targets. This review will represent the complete medicinal and pharmacological profile of pyrido[2, 3- d ]pyrimidines as anticancer agents, and will help scientists to design new selective, effective and safe anticancer agents.